The Psycho-Physiological Profile of Adolescent Elite Sailors: Testing a Three-Way Moderation Model - Valenzano, Anna Antonia; Monacis, Lucia; Ceglie, Flavio; Messina, Giovanni; Polito, Rita; Sinatra, Maria; Cibelli, Giuseppe (Frontiers in Psychology, 2020)
The present study aimed at extending the work on individual differences in the relationships between personality traits and the cortisol response, by examining the interaction effects of sex and role category in Italian adolescent elite dinghy sailors. Seventy athletes completed a self-reported questionnaire including socio-demographic data, information about the role played on board (helmsmen or bowmen) and the Big Five Questionnaire-2. Salivary cortisol samples were collected at 30 min after awakening the day before competitions. Main findings from bivariate correlations showed positive associations among cortisol levels, extraversion and consciousness in both male and female bowmen groups. The moderation and moderated moderation analyses further indicated (1) a three-way interaction effect in the relationship between extraversion and salivary cortisol, (2) a marginal significant three-way interaction effect in the relationship between neuroticism and salivary cortisol, (3) no other personality dimensions were significantly predictive of the outcome variable. Our results provided evidence not only about sex differences, but also about the role played on board by the sailors in the linkages between personality traits and the biomarker of the trait component of HPA axis functioning.